The impact of environmental policy on renewable energy innovation: A systematic literature review and research directions - Rastegar H; Eweje G; Sajjad A (ERP Environment and John Wiley and Sons Ltd, 2024)
Renewable energy innovations are imperative to tackle the climate change crisis. However, there is a gap in the literature regarding the effectiveness of environmental policies in promoting renewable energy innovations. To bridge this gap, we have adopted a systematic literature review process covering the period from 2005 to 2023. We identified and analysed 29 articles in our final sample. Further, we employ two levels of analysis (individual-policy and policy-mix levels) for analysing the extant research. Our findings show that fiscal incentives and emissions trading policies such as the European Union (EU) Emissions Trading System (ETS) consistently promote renewable energy innovations. In contrast, the effectiveness of feed-in tariffs and quotas in supporting renewable energy innovations varies, reflecting diverse impacts across distinct regions and renewable energy technologies. Our analysis also suggests that combinations of various policy types can enhance innovation more effectively than individual policies. We contribute to the extant literature by developing a classificatory analysis of the effect of environmental policies on renewable energy innovations. Our review also provides research directions for future scholarship.
Keywords: environmental policy; individual-policy level; policy-mix level; renewable energy innovation